Sustainable urban development on the bicentennial of independent Peru: a priority issue on the 2021-2026 political agenda - Villalobos Villalobos, Vicente Brayan (2021)
The disorderly and spontaneous grow of cities and population centers is a characteristic of the Peruvian urbanism that is impossible to deny. In this regard, the housing deficit and the informal occupation of land, the impairment of the environment, and the deterioration of the cultural heritage of the nation are problematics that require priority attention.  In this article, the author aims to expose the inefficient planning of the Peruvian State in urban development based on the three problematic axes mentioned above. Along the same lines he argues that a key factor in these problems has been regulatory inconsistency; therefore, it develops the main historical antecedents of Peruvian urban planning legislation, in order to demonstrate that state disarticulation in the management of land use is a characteristic of national urbanism. Lastly, he addresses the reasons why he considers that the enactment of the recent Law on Sustainable Urban Development, is the beginning of a serious urban planning in Peru.